2004
DOI: 10.1002/adma.200400392
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Field‐Effect Transistor Behavior at Self‐Organized Interfaces

Abstract: sion-like behavior behind the leading edge of the phase front was not captured. The assumption of a fixed electron density did not take into account the important fact that additional electrons are transferred to the polymer once charge neutrality is re-established locally by the arrival of the cation front. Also, the assumption that the diffusion constant is fixed, rather than a function of the oxidation level, is not valid, as shown by the striking differences in shape and velocity during the first-ever redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
147
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 23 publications
3
147
0
Order By: Relevance
“…12 Indeed, smoothening of the semiconductor/dielectric interface has been shown to increase in the carrier mobility down to a minimum surface roughness. 28 On the other hand, the effects of interfacial trap states are hard to isolate from the bulk trap states within a semiconductor. Although methods exist to separate the two, they rely on specialized techniques such as ionizing radiation, 23 temperature dependent capacitance measurements, 24 or photo-excited charge-collection spectroscopy.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…12 Indeed, smoothening of the semiconductor/dielectric interface has been shown to increase in the carrier mobility down to a minimum surface roughness. 28 On the other hand, the effects of interfacial trap states are hard to isolate from the bulk trap states within a semiconductor. Although methods exist to separate the two, they rely on specialized techniques such as ionizing radiation, 23 temperature dependent capacitance measurements, 24 or photo-excited charge-collection spectroscopy.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…As schematically shown in Figure 2c, insulator polymer-top/organic semiconductor-bottom blended film can be utilized to simultaneously fabricate semiconductors and dielectrics. Chua et al, succeeded in fabricating a divinyl-tetramethyldisiloxane-bis(benzocyclobutene) (BCB)-top/poly(9,9-dialkylfluorone-alt-triarylamine) (TFB)-bottom bilayered structure by spin casting a BCB: TFB blended solution in mesitylene [23]. Figure 5a shows a ternary phase diagram of the BCB: TFB: mesitylene system.…”
Section: Vertical Phase-separationmentioning
confidence: 99%
“…Processing conditions such as spin speed during spin casting strongly affect the phase-separation kinetics. In one study, vertical phase-separation occurred under a specific spin speed of spin-casted polymer blends [23]. Because of a preference for vertically phase-separated polymer blends, many researchers have tried to fabricate vertically phase-separated structures using polymer blends [21].…”
Section: Fundamental Aspects Of Phase Separationmentioning
confidence: 99%
“…[12,13] Controlling the phase separation in the direction perpendicular to the substrate to form bilayer structures should be an effective way to diminish this effect because it allows retention of the connectivity of the semiconducting layer in the channel region. To this end, organic-semiconductor/dielectric-polymer blends with vertical phase separation have been used to fabricate high-performance TFTs with low operating voltage [14] or with improved environmental stability [15] at high semiconductor concentration (!40%). In a recent publication, [16] Goffri et al reported that the concentration of semiconductor in crystalline/crystalline bicomponent semiconductor/dielectricpolymer systems can be reduced to a value as low as 3 wt % without any degradation in device performance.…”
mentioning
confidence: 99%